Digital humanities strategies in transcultural studies - Arnold, Matthias; Decker, Eric; Volkmann, Armin (Universitätsbibliothek Heidelberg, 2017)
In this article the authors discuss the Digital Humanities strategies of Heidelberg University’s interdisciplinary Cluster of Excellence “Asia and Europe”. It describes the structures, methods, workflows and tools that have been established in Transcultural Studies research to profit from Digital Humanities research. It introduces a schematic workflow of typical humanities research within the Cluster’s digital research environment developed by the Heidelberg Research Architecture (HRA). The authors discuss challenges and solutions on the way towards sustainable digital research and education in the field of Transcultural Studies.